The Importance of Cardioprotective Artificial Ventilation of The Lungs in Intensive Care - Pulatova Sh.Kh; Ganiev N.S (Genius Journals, 2022)
This article deals with the importance of the cardof ioprotective ventilation in intensive care units and changes in patients who are under treatment for a long time in critical condition. In total, this year, 200 patients with traumatic brain injuries were treated in the neuroresistance department of the RSTEIM BF. 85 of these patients were connected to the OSV device. When examining 55 patients, 40 observed various changes in cardiovascular and respiratory Systems. The article describes X-ray studies, laboratory tests and ECG changes in these patients
Keywords: ventilation; closed craniocerebral injury; cardioprototype of USV